Legal Protection of Consumers in the Digital Business World - Muslim, Muslim; Aituru, Yulianus Payzon; Upara, Abdul Rahman (Jurnal Hukum dan Keadilan, 2025)
This article aims to analyze the legal protection of consumers in digital business in Indonesia. With a normative juridical approach, this study examines applicable regulations and the implementation of legal protection for consumers who transact online. The analysis was carried out on the Consumer Protection Law (UUPK), Government Regulations, and other regulations related to electronic transactions and data security. The results of the study show that although there are various regulations that regulate consumer protection in digital businesses, there are still various challenges in their implementation. Lack of consumer awareness, weak law enforcement, and the complexity of digital transactions are the main obstacles in consumer protection. Therefore, a strategy to increase digital literacy, strengthen regulations, and increase supervision in digital business practices is needed so that consumer rights can be optimally protected